2019
DOI: 10.22456/1679-1916.99522
|View full text |Cite
|
Sign up to set email alerts
|

Dispositivos móveis como ferramentas facilitadoras no processo de ensino-aprendizagem em fundoscopia

Abstract: A fundoscopia é fundamental no diagnóstico de doenças oculares e sistêmicas,porém, pouco priorizada na educação médica. Os dispositivos móveis estão cada vez mais inseridos no contexto da educação médica, sendo portanto, essencial a sua utilização com finalidades educacionais. Esse estudo objetivou: desenvolver um aplicativo para dispositivos móveis para facilitar o processo de ensino-aprendizagem em fundoscopia e retinopatia diabética (RD) destinado a estudantes de medicina; avaliar a sua usabilidade e utilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…In terms of the Flesch Readability Index, the booklet was classified as "very easy", with a score of 90 per cent. [11].…”
Section: Interventional Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the Flesch Readability Index, the booklet was classified as "very easy", with a score of 90 per cent. [11].…”
Section: Interventional Studymentioning
confidence: 99%
“…In their cross-sectional research into the development of a mobile application designed to facilitate the teaching and learning of medical students about fundoscopy and diabetic retinopathy, Damasceno et al [11] demonstrated that the technology shown is very usable and is considered a useful tool for student learning. This is due to the fact that digital images of the retina can be easily obtained using an adapter.…”
Section: Category 2 -Benefits Of the Applicability Of Ophthalmologica...mentioning
confidence: 99%